(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article gives an idea of the special tools and standards used in improving the effectiveness of training of 11-12-year-old students engaged in school athletics clubs. The also giving practical recommendations regarding the development of endurance of young athletes.